HUBUNGAN PEMAKAIAN DISPOSIBLE DIAPERS DENGAN KEJADIAN RUAM POPOK PADA BAYI USIA 0-12 - Kristin Natalia Napitupulu (Fakultas Kebidanan Institut Kesehatan Deli Husada, 2021)
Diaper rash is often caused by the use of the wrong diaper because does not immediately change the diaper after the baby urinates and defecates. If stool mixes with urine, there will be formation of ammonia (a substance from baby feces) which causes increased acidity of the skin resulting in irritation to the baby's skin. Usually also occurs because using disposable diapers exceeds the capacity, the skin becomes moist, so that friction occurs, the skin is easily irritated, this facilitates the growth of germs and fungi. Aim : To find out the relationship of use diapers with the incidence of diaper rash in infants aged 0-12 months. This study is an analytical study with a cross sectional study design with a sample of 15 taken by porposive sampling technique. Data analysis used bivariate analysis with chi-square test statistic test. Result : It can be seen that of the 15 respondents, most of the babies using dispossible diapers were 9 people (60.0%) who had diaper rash as many as 8 people (53.3%) and those who did not experience diaper rash were 1 person (6.7%) while babies who did not use dispossible diapers were 6 people (40.0%), and those who did not experience diaper rash were 6 people (40.0%).